Suspected gut barrier disruptors and development of food allergy: Adjuvant effects and early immune responses - Drønen, Elena Klåpbakken; Namork, Ellen; Dirven, Hubert; Nygaard, Unni Cecilie (Frontiers in Allergy, 2022)
Food allergy is an increasing public health challenge worldwide. It has recently been hypothesized that the increase in exposure to intestinal epithelial barrier-damaging biological and chemical agents contribute to this development. In animal models, exposure to adjuvants with a food allergen has been shown to promote sensitization and development of food allergy, and barrier disrupting capacities have been suggested to be one mechanism of adjuvant action. Here, we investigated how gut barrier disrupting compounds affected food allergy development in a mouse model of peanut allergy. Sensitization and clinical peanut allergy in C3H/HEOuJ mice were assessed after repeated oral exposure to peanut extract together with cholera toxin (CT; positive control), the mycotoxin deoxynivalenol (DON), house dust mite (HDM) or the pesticide glyphosate (GLY). In addition, we investigated early effects 4 to 48 hours after a single exposure to the compounds by assessing markers of intestinal barrier permeability, alarmin production, intestinal epithelial responses, and local immune responses. CT and DON exerted adjuvant effects on peanut allergy development assessed as clinical anaphylaxis in mice. Early markers were affected only by DON, observed as increased IL-33 (interleukin 33) and thymic stromal lymphopoietin (TSLP) alarmin production in intestines and IL-33 receptor ST2 in serum. DON also induced an inflammatory immune response in lymph node cells stimulated with lipopolysaccharide (LPS). HDM and GLY did not clearly promote clinical food allergy and affected few of the early markers at the doses tested. In conclusion, oral exposure to CT and DON promoted development of clinical anaphylaxis in the peanut allergy mouse model. DON, but not CT, affected the early markers measured in this study, indicating that DON and CT have different modes of action at the early stages of peanut sensitization.